APPLICATION OF DISCOVERY LEARNING MODEL WITH CONCRETE MATERIALS TO IMPROVE MATHEMATICS LEARNING ABOUT PLANE FIGURES TO FOURTH GRADE STUDENTS OF SD NEGERI 2 TAMANWINANGUN IN ACADEMIC YEAR OF 2019/2020. - Rezkia Widya Safitri; Wahyudi Wahyudi; Ngatman Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The objectives of the research were: (1) describing the steps to the application of Discovery Learning model with concrete materials, (2) improving mathematics learning about plane figures through Discovery Learning model with concrete materials, (3) analyzing obstacles and solutions of applying the Discovery Learning model with concrete materials.The research was a collaborative classroom action research (CAR) conducted in three cycles. There were two meetings in each cycle. A meeting consisted of planning, implementing, observing, and reflecting. The subjects were 25 students of fourth grade of SD Negeri 2 Tamanwinangun in academic year of 2019/2020. The data used in the form of qualitative data were the application of the Discovery Learning model with concrete materials while quantitative data were the results of mathematics test. Data collection techniques included observation, interviews, and tests. The validity of the data used triangulation of techniques and triangulation of sources. Data analysis included data reduction, data presentation and drawing conclusions.The results showed that: (1) the steps to the application of the Discovery Learning model with concrete materials to improve mathematics learning about plane figures were: (a) giving stimulation by concrete materials, (b) writing problem statements, (c) collecting data, (d) processing data, (e) verifying, (f) making generalization; (2) the application of Discovery Learning model with concrete materials improved mathematics learning about plane figures to fourth grade students of SDN 2 Tamanwinangun in academic year of 2019/2020. It was proven by the results of teacher observation, student observation, and learning outcomes. The results of teacher observation were 85.71% in the first cycle, 87.38% in the second cycle, and 90.17% in the third cycle. The results of student observation were 85.57% in the first cycle, 87.50% in the second cycle, and 90.17% in the third cycle. Student learning outcomes were 88% in the first cycle, 92% in the second cycle, and 94% in the third cycle; (3) the obstacles were: (a) the teacher faced lack of class mangement when students were not paying attention, (b) some students were passive in group discussion therefore the discussion took much time. The solutions provided by the researcher were (a) the teacher improved the class management, (b) the teacher gave tasks to the students equally and managed the time management.It concludes that application of Discovery Learning model with concrete materials improves mathematics learning about plane figures to fourth grade students of SD Negeri 2 Tamanwinangun in academic year of 2019/2020.Keywords: Discovery Learning, Concrete Materials, Mathematics